Growth, yield and water use efficiency of wheat in silt loam-amended loamy sand (Journal of the Bangladesh Agricultural University, 2010)
This study investigated the growth, yield and water use efficiency of wheat in five soil textures obtained by amendment. This was done by executing field experiments that consisted of five soil treatments with 3 replications. The treatments were: (i) T1: loamy sand, (ii) T2: sandy loam, (iii) T3: loam 1, (iv) T4: loam 2 and (v) T5: silt loam (used as amendment). Wheat was cultivated with four irrigations and recommended dose of fertilizers. Increased porosity and pore size distribution in the finer-textured soils improved soil structure with a consequent improvement in soil physico-chemical properties. The saturated hydraulic conductivity decreased significantly, while field capacity and water retention increased considerably as the textured of the soil become finer. The improved water and organic matter contents in treatments T2 - T5 stimulated growth of wheat and caused significant (p = 0.05) increase in leaf area index, plant height, number of total and effective tillers per plant, spike length, number of spikelets per spike, number of grains per spike, grain yield, and biological yield compared to T1. The roots grew and branched profusely in the soil of high moisture and organic matter content; the largest root biomass was in the upper 20 cm of soil depth in all the treatments. The enhanced vegetative growth in terms of plant height and number of tillers per plant helped increasing straw yield, which together with yield attributing characters, improved the biological yield in the finer textured soils. Treatments T2 - T4 produced 1.2 to 2.8 times higher grain and biological yields compared to T1. The irrigation requirement and total water used in a treatment increased as the texture of a soil became coarser. Treatment T2 saved 1 to 13.6% and T3- T5 saved 29.4 to 57.5% irrigation water compared to T1. T1 provided the lowest water use efficiency, which increased gradually as the texture became finer. All treatments except T1 maintained improved water regime. Keywords: Clay content; Soil water; Wheat cultivation; Growth and yield; Water use efficiency DOI: 10.3329/jbau.v7i2.4753 J. Bangladesh Agril. Univ. 7(2): 403-410, 2009